Feasibility of Silicon Addition to Boron Foliar Spraying in Cauliflowers - da Silva, José Lucas Farias [UNESP]; Prado, Renato de Mello [UNESP]; de Souza Junior, Jonas Pereira [UNESP]; Tenesaca, Luis Felipe Lata [UNESP]; da Silva, Dalila Lopes [UNESP]; Pinsetta Junior, José Sidnaldo [UNESP] (Springer Nature, 2021)
Our objective was to assess the feasibility of foliar spraying of boron (B) with the addition of silicon (Si) to the spray solution and its effects on the alleviation of oxidative stress and physiological damages induced by B deficiency in cauliflowers. An experiment was carried out between March and August 2019 with cauliflower plants of the cultivar Quatro Estações. Treatments comprised four B concentrations (0, 0.11, 0.25, and 0.42 g L−1), as well as the absence and presence of Si (12 mmol L−1). Boric acid (17.5% B) was used as a source of B. Potassium silicate (115.2 g L−1 Si and 113.85 g L−1 K2O) (SiK2O3) stabilized with sorbitol was used as a source of Si. During the experiment, nine foliar applications were carried out every 10 days, using a manual sprayer. The absorption of B by cauliflower leaves increased when silicon was added to the spray solution. Moreover, Si addition relieved oxidative stress by decreasing MDA and H2O2 contents and increasing phenolic compounds and ascorbic acid. Si addition also improved leaf tissue firmness, photosynthetic pigment production, PSII quantum efficiency, and hence plant growth. As a conclusion, adding Si to the foliar spray solution of B is feasible for growing of cauliflowers.
Keywords: Beneficial element; Brassica oleracea var. botrytis; Micronutrient; Nutritional stress